Differential diagnosis of heavily pigmented melanocytic lesions: challenges and diagnostic approach. Issue 12 (23rd November 2015) - Aung, Phyu P; Mutyambizi, Kudakwashe K; Danialan, Richard; Ivan, Doina; Prieto, Victor G
Abstract : The differential diagnosis of heavily pigmented melanocytic neoplasms includes melanoma (especially animal type), melanosis of partially or completely regressed melanoma, blue naevus (BN), pigmented Spitzoid lesions, recurrent naevus, combined naevus, pigmented spindle cell naevus, epithelioid blue naevus of the Carney complex/pigmented epithelioid melanocytoma, deep penetrating naevus, hyperpigmented scar after surgery of melanoma in which there are also melanophages and hyperpigmentation due to the minocycline, a tattoo or a hyperpigmented scar. Pathologists face challenges when evaluating a pigmented lesion, especially in a small superficial biopsy, because it is difficult to access important histopathological features to differentiate benign versus malignant melanocytic lesions. The histological features that favour a diagnosis of melanoma include dimension (>6 mm), asymmetry, poor circumscription, irregular confluent nests, confluent lentiginous junctional melanocytic proliferation, lack of maturation with descent in the dermis, suprabasal pagetoid melanocytes, asymmetrical distribution of melanin pigment, cytological atypia, dermal mitotic figures, asymmetrical dermal lymphocytic infiltrate and necrosis.